DA+ data acquisition and analysis software at the Swiss Light Source macromolecular crystallography beamlines. (8th December 2017) - Wojdyla, Justyna Aleksandra; Kaminski, Jakub W.; Panepucci, Ezequiel; Ebner, Simon; Wang, Xiaoqiang; Gabadinho, Jose; Wang, Meitian
Abstract : The implementation of DA+ data acquisition and analysis software at Swiss Light Source macromolecular crystallography beamlines is presented. Detailed descriptions of the user interface, acquisition engine, online processing and database, which are the major components of DA+, are given. Abstract : Data acquisition software is an essential component of modern macromolecular crystallography (MX) beamlines, enabling efficient use of beam time at synchrotron facilities. Developed at the Paul Scherrer Institute, the DA+ data acquisition software is implemented at all three Swiss Light Source (SLS) MX beamlines. DA+ consists of distributed services and components written in Python and Java, which communicate via messaging and streaming technologies. The major components of DA+ are the user interface, acquisition engine, online processing and database. Immediate data quality feedback is achieved with distributed automatic data analysis routines. The software architecture enables exploration of the full potential of the latest instrumentation at the SLS MX beamlines, such as the SmarGon goniometer and the EIGER X 16M detector, and development of new data collection methods.